Blood pressure profile is associated with microalbuminuria and retinopathy in hypertensive nondiabetic patients - ÖZBEN SADIÇ, BESTE (SPRINGER WIEN, 2018)
Target organ damage is important for global cardiovascular risk assessment. The aim of this study was to explore the association between the blood pressure profile and end-organ damage in a hypertensive non-diabetic cohort. A total of 560 consecutive hypertensive nondiabetic patients (mean age: 58.2 +/- 13.3 years, 221 men) were included in the study. All patients underwent thorough physical examination including fundoscopic examination. First morning urine samples were obtained from each patient and measurement of the albumin-to-creatinine ratio in first morning urine collection samples was used for diagnosis of microalbuminuria. All patients underwent a 24-h ambulatory blood pressure monitoring and were grouped as dippers and non-dippers according to the presence or absence of > 10% decrease in blood pressure during the night, respectively. The non-dipper group consisted of 247 patients with a non-dipper blood pressure profile, 31 patients with reverse dipping and 4 patients with extreme dipping. Non-dipper patients were significantly older. Coronary artery disease, cerebrovascular disease, hypertensive retinopathy and microalbuminuria were significantly more prevalent in the non-dipper patients. Non-dipping hypertension increased the risk of hypertensive retinopathy by 1.89 times (95% confidence interval, CI:1.35-2.65, p < 0.001) and the risk of microalbuminuria by 2.23 times (95% CI:1.49-3.33, p < 0.001). Non-dipping hypertension was still significantly associated with hypertensive retinopathy and microalbuminuria when adjusted by age and sex. Non-dipping hypertension was associated with increased risk of hypertensive retinopathy and microalbuminuria. Blood pressure profiles should also be considered in assessing the risk for hypertensive patients.
Keywords: Non-dipping; Hypertension; Microalbuminuria; Retinopathy; TARGET ORGAN DAMAGE; DIPPING PATTERN; RISK; DIPPER; METAANALYSIS; MORTALITY; FALL